Telaah Pemanfaatan Media Pembelajaran Berbasis Video pada Buku Tematik Kelas III SD/MI - Frasandy, Rendy Nugraha; Astuti, Ria; Yuliantika, Sonya; Septiana, Nyangfah Nisa (Universitas Islam Negeri Imam Bonjol Padang, 2024)
The purpose of the study was to determine the utilization of video learning media in thematic books theme 1 subtheme 1 at the SD / MI level. This type of research uses library research. The research data sources are journals and thematic books on “Growth and Development of Living Things” Class III SD, and using books and journals relevant to this research. The data collection technique used is documentation. Then the data is processed through data collection, reduction, interpreting and analyzing the data. The results of this study reveal about the utilization of video learning media educators explain thematic learning material first, then learning activities are continued with educators inviting students to actively participate in learning through questions and answers related to thematic learning material, after which educators play video learning media. The learning media used must have their own advantages and disadvantages, as well as video media. In viewing the video cannot stand alone, this video media requires supporting tools such as LCD to project images and active speakers to display sound to be heard clearly.